Systematics, biogeography and host-plant relationships of the Neotropical jumping plant-louse genus Russelliana (Hemiptera: Psylloidea) - Serbina, Liliya; Burckhardt, Daniel (Zootaxa, 2017)
The Neotropical genus Russelliana (Psyllidae: Aphalaroidinae) is revised and its phylogenetic, host-plant and biogeographical relationships are discussed. Twenty-four species are described as new, bringing the number of known species to 43. An identification key is provided for the adults. A phylogenetic analysis of 26 morphological characters resulted in 54 most parsimonious trees. The consensus tree is well resolved at the base but poorly at the crown. Most Russelliana species are monophagous or oligophagous with the exception of R. solanicola which is polyphagous. With eight plant families, the host range of Russelliana is broader than that of other aphalaroidine genera. The hosts for 29 species are confirmed, those for 12 species are suggested based on phylogenetic relationships. The species associated with Asteraceae (4 spp.) and most of the Fabaceae-feeders (12 spp.) form each a monophyletic group, those associated with Verbenaceae (5 spp.) are paraphyletic and those with Solanaceae are polyphyletic (16 spp.). The two species associated with Rosaceae are not closely related. These patterns suggest repeated host shifts. Whether there is cospeciation in some groups cannot be judged as neither psyllid nor host phylogenies are sufficiently resolved. The world psylloid fauna comprises relatively few species associated with Solanaceae. The number of 16 Russelliana species with confirmed or likely solanaceous hosts is, therefore, surprising and important in view of the potential pest status of some Russelliana spp. The genus is restricted to temperate and subtropical South America (Argentina, Bolivia, Southern Brazil, Chile, Peru and Uruguay). Most species are known from the Western Andean part of the continent. Only four species are currently known from Eastern South America. The cladogram suggests that geographical vicariance may account for at least part of the observed species richness, as five vicariant events were detected for Russelliana. A better resolution of the cladogram may reveal more cases of geographical vicariance.